Academic performance disparities across gender in entrepreneurship course / Nur Fadhlina Zainal Abedin, Faridah Pardi and Asma' Rashidah Idris - Zainal Abedin, Nur Fadhlina; Pardi, Faridah; Idris, Asma' Rashidah (2021)
In the age of unprecedented global and technological transformation, the education ministry through higher learning institutions such as universities has progressively designed various learning programs for students to adapt to skills that had been neglected or not been the point of focus in the curriculum before. As a reflection of this, entrepreneurship education has emerged out as a demanding subject and has been made compulsory for public university students in Malaysia. Introduced into the education system a few decades ago, the effectiveness of entrepreneurship learning programs should be consistently addressed to ensure quality in academic performance. Issues surrounding academic performance such as gender difference have become a central debate to highlight the virtue of learning success. At Universiti Teknologi MARA (UiTM), the entrepreneurship subject is coded as ENT300 (Fundamentals of Entrepreneurship) and is mandatory for all undergraduate program students. ENT300 has been perceived as a non-technical subject. Due to this, people tend to assume that it is a readingbased subject where female students would perform better as compared to male students. Hence, the main question posed in this study is: is it true that there are disparities in gender performance in the ENT300 course? To address this issue, we analyse ENT300 course marks between male and female students in the UiTM Negeri Sembilan branch. The findings may guide us in bringing innovative approaches for the future development of this subject discipline through effective learning platforms where practical entrepreneurial skills can be trained and amplified.